AKAD NIKAH ULANG SEBAGAI RITUAL MEMPEROLEH KETURUNAN DALAM TINJAUAN HUKUM ISLAM (STUDI KASUS PADA PASANGAN SUAMI ISTRI DI DESA TINGGEDE KEC. MARAWOLA KAB. SIGI) - Moh. Rizal; Muh. Syarif Hasyim; Sitti Nurkhaerah (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
Based on the research background that has been mentioned, the remarriage agreement as a ritual of obtaining offspring in a review of Islamic law, a case study of a married couple in the village of Tinggede, Kec. Marawola Kab. Sigi, then obtained several objectives from this study, namely to explain and describe how the process of remarriage contracts for couples in the village of Tinggede Kec .arawola, Kab. Sigi as a ritual to obtain offspring and how Islamic law review of the remarriage agreement to the couple in the village of Tinggede Kec.Marawola, Kab. Sigi as a ritual to get offspring. This study uses a qualitative approach with more emphasis on the relevance of the findings that occur in the field, so that the data can be presented in actual terms, the data collection technique used is the field of data collection techniques (field research). The intended data collection technique is collecting a number of data directly. The results showed that the process of implementing a marriage contract that occurred in couples in the village of Tinggede was as follows: firstly there was an underlying reason and secondly halal and haram re-marriage contracts were seen in terms of or the intention behind the process of a remarriage contract. So that in the Islamic religion, the glasses of Islamic law see this as a prohibition because of the descendants in a family, purely the gift of Allah. Humans can only endeavor, looking for reasons that are permitted by the Shari'a to get them.